Hubungan Tingkat Pengetahuan Pasien Glaukoma dengan Tingkat Kepatuhan Penggunaan Obat dalam Mengontrol Tekanan Intraokular di Klinik Mata Nusantara Jakarta Tahun 2024 - Rina Octavia; Asha Grace Sicilia; Pratiwi Cahya Wardhani; Dalva Gumilar (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2025)
Glaucoma requires lifelong treatment and has a high risk of causing blindness. Therefore, patient compliance is very important, including regular monitoring of intraocular pressure and use of medications as directed. Non-compliance can worsen the condition and increase medical costs. Objectives: This is to determine the relationship between the level of knowledge of glaucoma patients and the level of compliance in using drugs to control intraocular pressure at the Nusantara Eye Clinic, Jakarta in 2024. Methods: is a quantitative study with a Cross Sectional approach. The research sample was 58 patients using purposive sampling technique. The anxiety measurement instrument used a questionnaire on the level of knowledge and compliance with drug use. Data were analyzed using the Spearman rank test and presented in the form of a frequency distribution table. Results: howed high knowledge (94.4%) and the variable level of drug compliance in the moderate category (50%). Based on statistical tests using the Spearman Rank correlation test, a significance level of p-value = 0.000 was obtained, so it can be concluded that there is a relationship between the level of knowledge of glaucoma patients and the level of drug compliance in controlling intraocular pressure at the Nusantara Eye Clinic, Jakarta in 2024. The correlation coefficient in this study has a value of 0.448, which means that the relationship between these two variables is very strong and inversely related. Conclusion, There is a relationship between the level of knowledge of glaucoma patients and the level of compliance with the use of drugs in controlling intraocular pressure at the Nusantara Eye Clinic, Jakarta in 2024. Researchers are advised to develop further research by analyzing factors that influence compliance with treatment in glaucoma patients such as attitudes, motivation, perceptions, and beliefs.